2020
DOI: 10.1093/hmg/ddaa153
|View full text |Cite
|
Sign up to set email alerts
|

Rare deleterious BUB1B variants induce premature ovarian insufficiency and early menopause

Abstract: Losing of ovarian functions prior to natural menopause age causes female infertility and early menopause. Premature ovarian insufficiency (POI) is defined as the loss of ovarian activity before 40 years of age. Known genetic causes account for 25%—30% of POI cases, demonstrating the high genetic heterogeneity of POI and the necessity for further genetic explorations. Here we conducted genetic analyses using whole-exome sequencing in a Chinese non-syndromic POI family with the affected mother and at least four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Enrichment results implied that PDT process may participate into regulation of E2F-mediated gene transcription and further regulate expression of down-stream genes. For these genes, CDK1 is significantly up-regulated after the H 2 O 2 -induced oxidative stress by inactivating the PI3K/AKT signaling ( 38 ); CCNA2, CDC45 , and MCM4 are downstream genes of cyclin-dependent kinase inhibitor p16 in D-galactose-induced aging in mice ( 39 ); BUB1B is involved in cell division and induces the vulnerability for oxidative stress ( 40 ); PLK1 , as the serine/threonine-protein kinase gene, also plays a major role in chromosomal instability ( 41 ) and cell cycle progression ( 42 ). These hub genes indicated that low-dose PDT intervention induces may participate into regulation of cell cycle-related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment results implied that PDT process may participate into regulation of E2F-mediated gene transcription and further regulate expression of down-stream genes. For these genes, CDK1 is significantly up-regulated after the H 2 O 2 -induced oxidative stress by inactivating the PI3K/AKT signaling ( 38 ); CCNA2, CDC45 , and MCM4 are downstream genes of cyclin-dependent kinase inhibitor p16 in D-galactose-induced aging in mice ( 39 ); BUB1B is involved in cell division and induces the vulnerability for oxidative stress ( 40 ); PLK1 , as the serine/threonine-protein kinase gene, also plays a major role in chromosomal instability ( 41 ) and cell cycle progression ( 42 ). These hub genes indicated that low-dose PDT intervention induces may participate into regulation of cell cycle-related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…BUB1B variants cause ovarian insufficiency and early menopause. Several studies have shown that highly elevated BUB1B is associated with high OC cell proliferation and poor clinical prognosis ( Feng et al, 2019 ; Chen et al, 2020 ). Folate receptor 1 (FOLR1) is a glycosylphosphatidylinositol (GPI)-anchored glycoprotein, enriched in oocytes of primary, secondary, and tertiary follicles as well as in surrounding granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of spindle detection sites and a doubling of severe chromosome separation defects proved to be associated with BUB1B inactivation [40]. BUB1B mutated, resulting in reduced BUB1B expression, increased brittleness of antioxidant stress, and premature ovarian failure [41].…”
Section: Cep55 (Centrosome Protein) Is a Vital Component In Cell Cycl...mentioning
confidence: 99%